Machado de Assis e o risum movet do poema herói-cómico. Algumas cláusulas a propósito d’O Almada - Serra, Pedro G. (Diálogos Latinoamericanos, 2013)
O Almada, mock-epic poem written by Machado de Assis, proposes a ‘theory’ of this ‘difficult’ genre, within a literary program that would mean the invention of a first example of mock-epic poetry in Brazilian literature. Machado’s proposal implies that the mock-epic looses referentiality; otherwise put, undergoes a process of anesthetization. This aesthetic autonomy, however, would signify the universalization of a textual phenomenology of “two famous compositions that served as models, but are not truly inimitable”. In my article I elaborate on how Machado de Assis reads the mock-epic tradition, Boileau’s Le Lutrin and specifically António Dinis da Cruz e Silva’s O Hissope.